GABA-Producing Natural Dairy Isolate From Artisanal Zlatar Cheese Attenuates Gut Inflammation and Strengthens Gut Epithelial Barrier in vitro - Sokovic Bajic, Svetlana; Djokic, Jelena; Dinic, Miroslav; Veljovic, Katarina; Golic, Natasa; Mihajlovic, Sanja; Tolinacki, Maja (Frontiers in Microbiology, 2019)
Probiotic bacteria are recognized for their health-promoting properties, including maintenance of gut epithelial integrity and host immune system homeostasis. Taking into account the beneficial health-promoting effects of GABA, the presence of the gadB gene, encoding glutamate decarboxylase that converts L-glutamate to GABA, was analyzed in Lactic Acid Bacteria (LAB) natural isolates from Zlatar cheese. The results revealed that 52% of tested Lactobacillus spp. and 8% of Lactococcus spp. isolates harbour the gadB gene. Qualitative and quantitative analysis of GABA production performed by Thin-Layer Chromatography (TLC) and High-Performance Liquid Chromatography (HPLC) revealed the highest GABA production by Lactobacillus brevis BGZLS10-17. Since high GABA-producing LAB natural isolates are the most valuable source of naturally produced GABA, the probiotic properties of BGZLS10-17 were characterized. This study demonstrated high adhesion of BGZLS10-17 strain to Caco-2 cells and the ability to decrease the adhesion of Escherichia coli ATCC25922 and Salmonella enterica C29039. Treatment of differentiated Caco-2 cells monolayer with BGZLS10-17 supernatant containing GABA alleviated inflammation (production of IL-8) caused by IL-1β and significantly stimulated the expression of tight junction proteins (zonulin, occludin and claudin 4), as well as the expression of TGF-β cytokine leading to the conclusion that immunosuppression and strengthening the tight junctions can have significant role in the maintenance of intestinal epithelial barrier integrity. Taken together the results obtained in this study support the idea that using of GABA producing BGZLS10-17 probiotic strain could be a good strategy to modulate immunological response in various inflammatory diseases, and at the same time, it could be a good candidate for adjunct starter culture for production of GABA-enriched dairy foods and beverages offering new perspectives in designing the novel functional foods.